The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/children10030510
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Fall Height, Fracture Severity and Clinical Outcome in Pediatric Supracondylar Fractures—A Retrospective Analysis with an Observation Period of 20 Years

Abstract: The most common cause leading to supracondylar humerus fractures in children is falling onto an outstretched arm. A correlation between fall height and fracture severity may be assumed but has not yet been described. The aim of this study was to show that fracture severity increases with fall height. Furthermore, the correlation between fracture severity and outcome was examined. A total of 971 children with supracondylar humerus fractures between January 2000 and December 2019 were included in this study. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 44 publications
1
6
0
1
Order By: Relevance
“…For our analysis, we categorized fractures based on fall height: a short distance or standing height (<1 m) or from a greater height (>1 m). We observed that the more severe fractures were statistically associated with falls from great heights, a finding that is consistent with those of Schuller et al 3 , who found that type I fractures typically occur during falls from standing height, while the severity of fractures seems to increase with fall height per the Gartland classification 3 .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…For our analysis, we categorized fractures based on fall height: a short distance or standing height (<1 m) or from a greater height (>1 m). We observed that the more severe fractures were statistically associated with falls from great heights, a finding that is consistent with those of Schuller et al 3 , who found that type I fractures typically occur during falls from standing height, while the severity of fractures seems to increase with fall height per the Gartland classification 3 .…”
Section: Discussionsupporting
confidence: 92%
“…Given the increasing incidence of supracondylar fractures of the humerus in children in recent years 3,14 , it is crucial to understand the epidemiological profile of these fractures across different regions of Brazil. With this aim, the present study undertook an epidemiological analysis of patients treated at a referral pediatric hospital in northeastern Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations